The suffixes -oso, -ento, -udo and -ón in Mexican Spanish: Interchange and productivity - Zacarías Ponce de León, Ramón Felipe (Círculo de Lingüística Aplicada a la Comunicación, 2022)
The Spanish suffixes -oso, -ento, -udo and -ón (lluvioso ‘rainy’, hambriento ‘hungry’, barbudo ‘bearded’, cabezon ‘big head person’) are included in the semantic space of suffixes that are used mainly to form qualifying adjectives (NGLE, 2010). The closeness between these affixes causes a rivalry that becomes evident through the large number of quasi-synonymous words that exist in Spanish. (Zacarías, 2016a): mugroso, mugriento ‘grimy’; caprichoso, caprichudo ‘whimsical’; barbudo, barbón ‘bearded’; lloroso, llorón,‘weepy’ etc. In this paper, from the onomasiological point of view (Štekauer, 2005a, 2005b, 2016), we will analyze these suffixes to establish the criteria that can distinguish their individual sphere of influence and the main characteristics of the words formed in each case. We will follow a methodology that has been used to study this type of competing suffixes, which distinguishes between structural and contextual factors. We will use data from attested words, both in dictionaries and in neologisms (Zacarías, 2016b), to describe the current trends in Mexican Spanish. Finally, it is shown that each suffix establishes its own domain of action and there exist quasisynonymous because this pairs of words are distinguished by subtle differences in meaning.